Response of mango ginger to plant population and different weed control methods in the forest – savannah transition agro-ecology of South-western Nigeria - Osunleti, Samuel; Lagoke, Segun (Journal of Agricultural Sciences (Belgrade), 2024)
Field trials were conducted in the early cropping seasons of 2016 and 2017 at the Teaching and Research Farm of the Federal University of Agriculture Abeokuta (07° 20ʹ N, 3° 23ʹ E 159 m above sea level) in the forest – savannah transition agro ecology of South-western Nigeria to evaluate the response of mango ginger to plant population and different weed control methods. Treatments were laid out in split plot arrangement in a randomized complete block design with three replications. The main plot consisted of two plant populations: 444,444 plants/ha and 250,000 plants/ha, while the sub plots consisted of ten weed control methods. Data collected on growth and yield of mango ginger, weed cover score and weed biomass were subjected to analysis of variance (ANOVA) and treatment means separated using 5% least significant difference (LSD at p ≤ 0.05). Planting mango ginger at 444,444 plants/ha gave significantly higher stand count and number of leaves than planting at 250,000 plants/ha. Different weed control methods gave significantly higher crop vigour score, number of leaves, stand count, yield and yield components than the weedy check. Relative to the highest in both years, uncontrolled weed infestation resulted in 91.4% rhizome yield reduction. There was 60.7% increase in mango ginger rhizome yield when post emergence weed control follows pre emergence weed control. Our study revealed that mango ginger being a long seasoned crop with initial slow growth, requires weed free situation beyond first 12 weeks after planting (WAP) for acceptable weed control and optimum rhizome yield.